Methods for neovagina creation in women with Mayer-Rokitansky-Küster-Hauser syndrome for subsequent uterus transplantation - Chmel, Roman; Pastor, Zlatko; Nováčková, Marta; Chubanovová, Nikoleta; Chmel, Roman (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
Mayer-Rokitansky-Küster-Hauser syndrome is a rare female congenital anomaly that presents with an inability to have coital sexual intercourse and absolute uterine factor infertility. Both surgical and nonsurgical approaches have been described for the treatment of vaginal agenesis to allow satisfactory coitus. Transplantation of the uterus has the challenge of achieving pregnancy and delivery of her own genetic and biological children in a woman without a natural uterus. Women of reproductive age with a congenital form of absolute uterine factor infertility are considered appropriate recipients of a uterus in the experimental phase of uterus transplantation trials. A neovagina in the normal anatomic position covered by natural non-keratinized mucosa is one of the main assumptions for surgical and reproductive success in transplant recipients. More than 70 uterine transplants have been performed to date, and more than 25 childbirths have been achieved by several research centers in the recipients of a uterus with uterine agenesis. In women with Mayer-Rokitansky-Küster-Hauser syndrome, skin-graft neovagina, Vecchietti's vaginoplasty, and self-dilation using Frank's and Ingram's methods are appropriate techniques to create a neovagina if transplantation of the uterus is intended in the future.
Keywords: Mullerian Ducts; dítě; Female; 46, XX Disorders of Sex Development; Infertility; poruchy sexuálního vývoje s karyotypem 46, XX; ductus Mülleri; uterus; lidé; infertilita; vrozené vady; Humans; ženské pohlaví; Congenital Abnormalities; Uterus; Child